Equity in health and justice: a look at the Brazilian Unified Health System (SUS) from the perspective of John Rawls - Machado Martins, Luiz Oscar; Fernandes dos Reis, Marcio; Chaoubah, Alfredo; Rego, Guilhermina (Acta Bioethica, 2023)
This study addresses the issue of equity in health and justice from the perspective of public health bioethics, describingthe Brazilian Unified Health System (SUS), equating legitimate interests for essential goods, such as health. The conceptionof John Rawls’ theory of justice is “justice as fairness” and has a seventeenth century contractualism tenor. Although it wasnot conceived specifically for health and marked by the “difference principle”, it promoted, in the field of health care, theinstitution of health systems created on the basis of universal access and equity in the distribution of scarce resources. Theprinciples of the Brazilian Unified Health System (SUS) guarantee access to all levels of care, equality in health care, withoutdistinctions or privileges of any kind, integrity in health care, free of charge, community participation and decentralization,regionalization and hierarchization of health actions and services, which gives the SUS a strong Rawlsian bias. The Brazilianmodel was built on the principle that health is a right of all and a duty of the State, therefore, it is based on the assumptionof universal and equal access to health actions and services for its promotion and recovery.